"Instantáneas", a modernist magazine in Santiago de Chile, 1900 - Mejías Alonso, Almudena; Clemente San Román, Yolanda (Revista General de Información y Documentación, 2018)
Chilean magazine Instantáneas, an illustrated periodical in the modernist style, was published in Santiago during the year 1900. After a thorough examination of the magazine’s numbers, a bibliographical-critical index has enabled us to study the literary and graphic contents. The article approaches the magazine’s history from a double perspective: on the one hand, its different sections and its Spanish and Spanish-American collaborators, editors, writers and artists; on the other, the important figures from contemporary society and from the artistic and literary world which were their principal subjects.
Keywords: Instantáneas; Illustrated magazines; Modernism; Chile; 19th Century.